A review on low temperature combustion engines: Performance, combustion and emission characteristics. (December 2019) - Krishnamoorthi, M.; Malayalamurthi, R.; He, Zhixia; Kandasamy, Sabariswaran
Abstract: Low temperature combustion (LTC) is a recent engine technology that can reduce the oxides of nitrogen (NOx) and soot emissions simultaneously while maintaining higher thermal efficiency. The present review work investigates the performance, emission and combustion characteristics of LTC mode engines. Partially premixed LTC (PPLTC), homogeneous charge compression ignition (HCCI), premixed charge compression ignition (PCCI) and reactivity controlled compression ignition (RCCI) modes are researched under LTC mode. In recent decades, different engine strategies have been employed to reduce exhaust emissions and to enhance thermal efficiency. Exhaust gas recirculation, variable valve timing (VVT), advanced fuel injection technologies are adapted to achieve LTC mode in internal combustion (IC) engines to get improved outcomes. This review highlights the properties of fuels, fuel supply systems, valve actuation mechanisms, engine operating conditions and its effects on the engine characteristics. This review provides a perspective plan to the researchers for enhancing the performance, emission and combustion behavior of an engine by using LTC mode with lower NOx and soot emissions. Among LTC mode engines, RCCI mode engine operates well in 60% load, 60% premixed ratio, 35:1 air-fuel ratio and 56% brake thermal efficiency within the combustion phasing control. Graphical abstract: Image 1 Highlights: LTC mode reduces NOx (85%), soot emissions (95%) and fuel consumption (15%). High ON and CN fuels supplied in PFI and DFI mode for combustion phasing control. RCCI mode is an advanced LTC mode engine which gives better outputs than other LTCs. About 55% thermal efficiency achieved in RCCI within Euro VI emission limits. LTC mode engines have more cycle-to-cycle variations above 60% engines loads.